ADVANCES IN PROTEIN SYNTHESIS TECHNOLOGY AND THEIR IMPLICATIONS FOR FUTURE PROTEIN AVAILABILITY: A NARRATIVE REVIEW - Wiwit Zuriati Uno; Siti Sulistiani Tompe; Salwa Miftahuljannah; Azqia Maharani Pulukadang; Farelia Rizkita Rahmadani J. Hako; Karim Putra Dunggio (JIMR : Journal Of International Multidisciplinary Research, 2025)
The availability of conventional protein sources is increasingly limited due to population growth, climate change, and limited land, so innovation is needed in providing more efficient and sustainable protein. This study aims to examine the development of protein synthesis technology and its implications for the availability of future protein sources. The method used is a literature review by examining scientific publications published from 2015-2024 searched through Google Scholar. The results of the study indicate that recombinant technology is able to produce high-quality functional proteins through genetic engineering of microorganisms, while microbial fermentation based on agro-industrial waste offers cheap and environmentally friendly Single Cell Protein production. In addition, increased production of poultry, eggs, and milk is the main support for the national animal protein supply. Overall, the development of protein synthesis technology provides a strategic opportunity to meet global protein needs through a resource-efficient, scalable, and sustainability-oriented approach.